Evaluation on Application Effect of MUIL in Tarim Oilfield - WANG Dongdong; LIU Shiwei; HOU Zhenyong (Cejing jishu)
With the deepening of the exploration and development of Tarim oilfield, the number of old wells has increased year by year, and the number of inefficient and ineffective old wells are increasing. Therefore, the comprehensive treatment needs of old wells has become urgent. It is particularly important to obtain accurate casing damage information before comprehensive treatment operations such as old well workover operations, window side drilling, and acid fracturing transformation of old wells. The multi-functiongal ultrasonic imaging logging tool (MUIL) uses ultrasonic pulse echo signal to realize casing loss detection, cementing quality and external medium phase evaluation, and provides accurate casing information such as casing deformation, change of casing wall thickness, casing perforation, casing misalignment, casing backconnection, etc. By comparing the logging application results of MUIL and 60-fingers multi-finger imaging tool (MIT) in casing leak detection and window side drilling and selection in Tarim oilfield, it is found that the casing loss detection results of the two are basically consistent, which verifies MUIL has a strong casing loss detection ability. In addition, the logging application results show that, MUIL in the selection of reservoir reconstruction and perforation level verification in Tarim oilfield can provide accurate casing information for reservoir transformation and verify the effectiveness of perforation position, and provide technical data support for engineering operations. Based on the MUIL logging results of workover wells in Tarim oilfield, 6 types of typical imagine characteristics are established to quickly identify the type of casing damage and provide guidance and assistance for subsequent engineering operations.